2018
DOI: 10.1016/j.ajo.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Graft Rejection in the Cornea Preservation Time Study

Abstract: Purpose: To identify factors related to graft rejection following Descemet stripping automated endothelial keratoplasty (DSAEK) in the Cornea Preservation Time Study (CPTS). Design: Cohort study within a multicenter randomized clinical trial. Methods: 1330 eyes of 1090 subjects undergoing DSAEK were randomized to receive a donor cornea with preservation time (PT) of 0–7 days (N=675) or 8–14 days (N=655) and followed for three years. Central endothelial cell density (ECD) was determined by a central image a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…A large national cohort study conducted by the National Health Service (NHS) Blood and Transplant in the UK showed that sex mismatched corneas were at a greater risk for failure, regardless of diagnosis or surgery type [ 8 ]. However, two recent studies from the US reported that donor-recipient sex combinations did not affect rejection episodes or graft survival [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large national cohort study conducted by the National Health Service (NHS) Blood and Transplant in the UK showed that sex mismatched corneas were at a greater risk for failure, regardless of diagnosis or surgery type [ 8 ]. However, two recent studies from the US reported that donor-recipient sex combinations did not affect rejection episodes or graft survival [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, partial graft dislocation was the most frequent complication observed (22 eyes) and has been always managed by early rebubbling. (8,(16)(17)(18)(19)(20). These multicentre, randomized trials evaluated the incidence of several factors on graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported by Sepsakos et al [ 4 ], as termination of steroid use was found to be the strongest risk factor for graft rejection. However, a more recent study did not find topical corticosteroid termination to be a significant factor predisposing to endothelial rejection after DSAEK [ 5 ]. In addition, close follow-up, especially in the first postoperative year, and subsequent long-term follow-up have been found by Wu et al to be the most important factor in varying immunologic graft rejection rates [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signs of endothelial graft rejection include keratic precipitates (KPs), corneal oedema and an anterior chamber reaction. According to different studies on Descemet stripping automated endothelial keratoplasty (DSAEK) complications, the 3-year incidence of immunologic graft rejection episodes ranges from 4 to 22% [1][2][3][4][5]. A recent study by Price et al found that endothelial rejection occurs in 7.9% of DSAEK cases over a 5-year period [6].…”
Section: Introductionmentioning
confidence: 99%